2003
DOI: 10.1086/378916
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cold Exposure Increases Skeletal Muscle Oxidative Structure and Function inMonodelphis domestica, a Marsupial Lacking Brown Adipose Tissue

Abstract: Monodelphis domestica (Marsupialia: Didelphidae) was used as a model animal to investigate and compare muscle adaptation to exercise training and cold exposure. The experimental treatment consisted of four groups of animals: either warm or cold acclimation temperature and with or without endurance exercise training. Maximal aerobic capacity during a running VO2max test in the warm-exercised or cold-exposed (with or without exercise) groups was about 130 mL O(2)/kg/min, significantly higher than the warm-acclim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…In contrast to the clear role of skeletal muscle shivering thermogenesis in thermoregulation early in cold acclimation, its role during prolonged cold exposure, when nonshivering is activated, is not clear. Recent data showed that sustained cold exposure in animals with brown adipose tissue causes metabolic and structural changes in skeletal muscle that indicate their shivering activity (Meyer et al, 2010;Mineo et al, 2012), similar to those observed following endurance exercise training (Schaeffer et al, 2003). It is known that shivering-related metabolic recruitment, in terms of fuel selection, can be achieved in three ways: (1) by recruitment of specific subpopulations of fibers within the same muscle; (2) by recruitment of muscles varying in fiber composition; and (3) by recruitment of different metabolic pathways within the same fibers.…”
Section: Introductionmentioning
confidence: 80%
“…In contrast to the clear role of skeletal muscle shivering thermogenesis in thermoregulation early in cold acclimation, its role during prolonged cold exposure, when nonshivering is activated, is not clear. Recent data showed that sustained cold exposure in animals with brown adipose tissue causes metabolic and structural changes in skeletal muscle that indicate their shivering activity (Meyer et al, 2010;Mineo et al, 2012), similar to those observed following endurance exercise training (Schaeffer et al, 2003). It is known that shivering-related metabolic recruitment, in terms of fuel selection, can be achieved in three ways: (1) by recruitment of specific subpopulations of fibers within the same muscle; (2) by recruitment of muscles varying in fiber composition; and (3) by recruitment of different metabolic pathways within the same fibers.…”
Section: Introductionmentioning
confidence: 80%
“…A clear supporting framework for these abilities is apparent in other species so far examined. As in 'athletic' placentals (Weibel et al, 2004;Weibel and Hoppeler, 2005), the peak aerobic demands associated with maximum energy output by muscle are met via the commensurate, matched oxygen supply system from the lungs to the muscle mitochondria via the expanded Sminthopsis crassicaudata data are from the present study; B. penicillata, M. rufus and M. domestica data are from previous studies Kram and Dawson, 1998;Schaeffer et al, 2003). Placental data are from Weibel et al (Weibel et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…The volume of muscle, its total mitochondrial content and its overall vascular supply were essentially identical in the Macropodiformes to values seen in 'athletic' placental mammals. Haim et al (1995), other data from Hoppeler et al (1984); rat-kangaroo (Bettongia penicillata) data from Dawson (2003, 2012); short-tailed opossum (Monodelphis domestica), BMR from Dawson and Olson (1988), other data from Schaeffer et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations